2023
DOI: 10.3390/ijms24021805
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Voltage-Gated Na+ Currents Exerted by KB-R7943 (2-[2-[4-(4-nitrobenzyloxy)phenyl]ethyl]isothiourea), an Inhibitor of Na+-Ca2+ Exchanging Process

Abstract: KB-R7943, an isothiourea derivative, has been recognized as an inhibitor in the reverse mode of the Na+-Ca2+ exchanging process. This compound was demonstrated to prevent intracellular Na+-dependent Ca2+ uptake in intact cells; however, it is much less effective at preventing extracellular Na+-dependent Ca2+ efflux. Therefore, whether or how this compound may produce any perturbations on other types of ionic currents, particularly on voltage-gated Na+ current (INa), needs to be further studied. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In recent studies, the instantaneous INa(W) current has been shown to be detectable during the short duration of an upwardly sloping (or ascending) ramp voltage (Vramp) in various excitable cells [23,28,29]. In this study, we investigated whether the presence of OM could alter the amplitude of the non-linear INa(W) that is elicited by a brief, upwardly sloping Vramp.…”
Section: Stimulatory Effect Of Om On the Window Component Of Ina (In(...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, the instantaneous INa(W) current has been shown to be detectable during the short duration of an upwardly sloping (or ascending) ramp voltage (Vramp) in various excitable cells [23,28,29]. In this study, we investigated whether the presence of OM could alter the amplitude of the non-linear INa(W) that is elicited by a brief, upwardly sloping Vramp.…”
Section: Stimulatory Effect Of Om On the Window Component Of Ina (In(...mentioning
confidence: 99%
“…The electrode used for the measurements typically had a tip resistance of 3-5 MΩ when filled with different internal solutions, as stated above. We measured different types of ionic currents in the whole-cell configuration using a modified patch-clamp technique with either an Axoclamp-2B (Molecular Devices, Sunnyvale, CA) or an RK-400 amplifier (Bio-Logic, Claix, France), as previously described [21][22][23]. We obtained GΩ-seals in an all-or-nothing fashion, resulting in a significant improvement in the signal-to-noise ratio.…”
Section: Electrophysiological Measurements With the Patch-clamp Techn...mentioning
confidence: 99%
“…Over the last decade, there has been a rapid increase in CADD-based studies of depression, including docking studies of ligands for serotonin reuptake [171,172], MAO A and MAO B [173,174], dual action on MAO-B/AChE [175], glycogen synthase kinase [176], sodium hNaV1.2 or hNaV1.7 channels [177], serotonin receptors (5HT1A, 5-HT2A, 5-HT2C and 5-HT4) [171,[178][179][180][181], adenosine A1/A2A receptors [182], T-type calcium channels [183], tryptophan 2,3-dioxygenase [184] and sigma receptor [185]. Similarly, application of docking in psychoses involved ligands for serotonin 5HT2 and dopamine D2 receptors [186], α4β2 and α7 nicotinic acetylcholine receptors [187,188], phosphodiesterase 10A [189], MAO A and B [190], a syntaxin-binding protein (STXBP1) [191], NMDA type subunit 1 (GRIN1) [192], fatty acid binding protein 7 (FABP7) [193,194], metabotropic glutamate mGluR5 receptor [195], ionotropic GABA-A receptor [196], glycine transporter type 1 (GlyT1) [197] and kynurenine aminotransferase II (KATII) [198].…”
Section: In Silico-driven Search For Novel Therapeutic Agentsmentioning
confidence: 99%
“…KN-R7943 (2-[2-[4-(4-nitrobenzyloxy)phenyl]ethyl]isothiourea) is an isothiourea derivative that is viewed to selectively suppress the reverse mode of NCX isoform 1 with an IC 50 value of 1.2–2.4 μM. However, a recent study by Wu and Yu [ 1 ] provided evidence that disclosed how, in pituitary GH 3 lactotrophs, cell exposure to KB-R7943 could inhibit a voltage-gated Na + current ( I Na ) in concentration-, time- and voltage-dependent manners. The yielded IC 50 values needed for KB-R7943 suppressed the amplitude of transient I Na ( I Na(T) ), and late I Na ( I Na(L) ) were distinguishable (i.e., 11 and 0.9 μM, respectively).…”
mentioning
confidence: 99%
“…Either benzamil or amiloride, also known to be inhibitors of the NCX exchanging current, was reported to inhibit an I Na(L) amplitude. When GH 3 cells were exposed to Ca 2+ -free, Tyrode’s solution, the deactivating I Na was progressively decreased in an exponential fashion as the duration of the depolarizing voltage step became prolonged [ 1 ].…”
mentioning
confidence: 99%